Evaluasi Usability pada Aplikasi Among Kota dengan Metode Think Aloud dan Heuristic Evaluation - Yan Giska Pranandita; Hanifah Muslimah Az-Zahra; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Among Kota is an application resulting from the implementation of the Smart City of Batu City, which acts as a medium to help the people of Batu City and tourists to find information about Batu City easier. The application, which was released on the Google Play Store on December 14, 2017, has received a rating of 4.1 out of a scale of 5. But behind this rating, various negative reviews from users regarding the application's usability have also emerged. Based on these problems, encouraging researchers to evaluate usability using the Think Aloud and Heuristic Evaluation methods. Evaluation is carried out to explore usability problems in the application in more depth from the perspective of users and experts, to be able to provide recommendations for proper interface design improvements to these problems. The evaluation using the Think Aloud method involving 8 respondents (users) resulted in 31 problems. Then, in the Heuristic Evaluation method that involved 4 evaluators (experts), 26 usability problems were identified and validated by all evaluators. Based on the evaluation results using the Think Aloud and Heuristic Evaluation methods above, then compiled into one and generated as many as 46 problems. Each problem is accompanied by a category of problem severity based on the severity rating it has. Furthermore, filtering and categorization are carried out to determine the problems given recommendations for improvement. Only issues that fall into the research scope categorized as Catastrophe and Major will be given suggestions for improvement. The result is 25 issues given suggestions for improving the new interface design, which the researcher presented in the form of a prototype.